М.О. Касаєва – одна із найперших співробітників відділу дендрології Національного ботанічного саду ім. М.М. Гришка НАН України - Klimenko, S.V.; Chuvikina, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Scientific activity and life path of M.O. Kasaeva – one of the first research worker of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine and her scientific work in Acclimatization Garden under the leadership of M.F. Kashchenko are delighted.